Strategi Bauran Pemasaran Bisnis Digital “Ngiklan Aja” dalam Meningkatkan Volume Penjualan - Shofia Syifa Ul Khasna; Yanda Bara Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the marketing strategies used by Ng Advertising Aja to increase its sales volume. The research method used is a qualitative descriptive method, using data collection techniques through interviews, observation and documentation. In-depth interviews were conducted to obtain information regarding the 7P marketing mix strategy, namely Product, Price, Place, Promotion, People, Process and Physical Evidence. which is used to find strengths, weaknesses, opportunities and threats using the SWOT analysis method. The results of this research are categorized into IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary). The resulting score from internal factors was 3.02; with a strength of 2.58 and a weakness of 0.44. Meanwhile, the score obtained from external factors was 3.48; with an opportunity of 2.66 and a threat of 0.82. Thus, it is known that Ng Advertising Aja is in quadrant I position, which supports the creation of an aggressive strategy by using its internal strengths to make the most of existing opportunities.